2021
DOI: 10.1084/jem.20210745
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophages rely on GM-CSF from alveolar epithelial type 2 cells before and after birth

Abstract: Programs defining tissue-resident macrophage identity depend on local environmental cues. For alveolar macrophages (AMs), these signals are provided by immune and nonimmune cells and include GM-CSF (CSF2). However, evidence to functionally link components of this intercellular cross talk remains scarce. We thus developed new transgenic mice to profile pulmonary GM-CSF expression, which we detected in both immune cells, including group 2 innate lymphoid cells and γδ T cells, as well as AT2s. AMs were unaffected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 83 publications
7
83
0
Order By: Relevance
“…By comparing scRNAseq and CITEseq data from COVID-19 lung samples with mini-bulk transcriptomic data of the various stages of fetal and postnatal AM development in wild type mice and GM-CSF-deficient mice, we found that recruited lung macrophages in COVID-19 lungs lack GM-CSF instruction. GM-CSF is the prime cytokine of the alveolar niche, produced by type II alveolar epithelial cells (AEC) 6 . This cytokine induces the master lipid-handling transcription factor PPARγ, and causes fetal and adult monocytes to differentiate into tissue resident AMs 5,7,41 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By comparing scRNAseq and CITEseq data from COVID-19 lung samples with mini-bulk transcriptomic data of the various stages of fetal and postnatal AM development in wild type mice and GM-CSF-deficient mice, we found that recruited lung macrophages in COVID-19 lungs lack GM-CSF instruction. GM-CSF is the prime cytokine of the alveolar niche, produced by type II alveolar epithelial cells (AEC) 6 . This cytokine induces the master lipid-handling transcription factor PPARγ, and causes fetal and adult monocytes to differentiate into tissue resident AMs 5,7,41 .…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine induces the master lipid-handling transcription factor PPARγ, and causes fetal and adult monocytes to differentiate into tissue resident AMs 5,7,41 . In adult mice, the return of tissue resident AMs following their depletion by infectious insults depends on GM-CSF production by type II AECs 6,56 . We have tried to measure GM-CSF levels in the BAL fluid of COVID-19 patients and other pulmonary infections but failed to detect it (data not shown), and serum levels of GM-CSF were very low in our cohort, despite an earlier report 45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that all embryonic macrophage populations (yolk sac-derived, fetal liver-derived, and bone marrow-derived) can independently colonize an empty alveolar niche and differentiate into functional AM suggests that the lung tissue produces maturation and development signals that can turn embryonic progenitors into differentiated AM. In this setting, the production of granulocyte macrophage colony-stimulating factor (GM-CSF) by the lung stroma, specifically by the alveolar epithelial type 2 cells [14], is vital since it induces the expression of the transcription factor peroxisome proliferator-activated receptor gamma (PPARG), a transcription factor essential for the differentiation and perinatal development of AM [15]. The role of GM-CSF is also supported by the demonstration that, in a situation of competition between progenitors, fetal liver progenitors, which have the highest affinity and avidity for this growth factor, become the main contributor to the replenishment of the alveolar niche [8].…”
Section: Maintenance Of the Alveolar Macrophage Niche During Homeostasismentioning
confidence: 99%